Sāli Rāmacandrarāya : Akṭōbar 10, 1888/1978, 31 Akṭōbar : saṃsmaraṇagaḷu - Paṭṭaṇaśeṭṭi, Siddhaliṅga (Sundara Pustaka Prakāśana, 1980)
On the life and works of Sāli Rāmacandrarāya, 1888-1978, Kannada litterateur; memoirs by Kannada writers.